Influence of heuristics and framing factors on speculating and investment behavior: Evidence from individual traders in the Saudi stock market / Ibrahim Tawfeeq Alsedrah - Alsedrah, Ibrahim Tawfeeq (2016)
Traditional finance (TF) assumes that people are rational. However, TF ignores the fact that people are human; their decisions, and subsequently, their behaviors, are influenced by emotions and psychology, especially when trading in the stock market. Therefore, Behavioral Finance (BF) has arisen to compliment TF. BF is a relatively new field that applies psychology to financial decisions and subsequently examines its effects on stock prices and the market. Most BF studies are conducted in developed markets, which are dominated by institutional investors. Most of these studies have used the experimental approach, and a few have used observation of trading accounts. However, there remains a lack of quantitative studies using surveys, especially in frontier markets like the Saudi Stock Market (SSM). The SSM is dominated by individuals who control around 90% of the market value. The market has witnessed stock mispricing, market inefficiency and sharp corrections, which have negatively affected individuals’ investments. Irrational behavior on the part of individuals is suspected to be the root of this problem. While many studies that have been published examine rationality in decision making in emerging and developed markets, little is known about the behavior of individuals in the Saudi stock market. In response to these issues, this research aims to determine the degree of heuristics and framing factors exhibited by individuals and to propose a theoretical model that explains the influence of heuristics and framing factors on individual speculating and investment buying behavior simultaneously. It then aims to quantify how much speculation and investment behavior is due to the influence of heuristics and framing factors. Lastly, it examines the role of experience in moderating the relationship between behavioral finance factors and individuals’ buying behavior. The model used was chosen based on a review of the literature and is empirically investigated using individuals trading in the biggest brokerage firms in Saudi Arabia. The findings of this research are drawn from 294 valid surveys collected from individuals trading in largest brokerage firms in Dammam, Riyadh and Jeddah City in the kingdom of Saudi Arabia. The Partial Least Square (PLS) approach to Structural Equation Modeling (SEM) is utilized in this research and SmartPLS version 2.0 software was used to analyze the empirical data. Analysis of the research model indicates that individuals exhibit a moderate degree of heuristics and framing factors during the decision making process. However, the results become more meaningful after examining the influence of these factors on the individuals’ buying behavior. The results indicate that confirmation heuristics, loss aversion and regret aversion influence speculation and investment behavior. Additionally, representativeness heuristics influence investment while anchoring influence speculation behavior. The analysis indicates that the majority of heuristics and framing factors introduced in this research model can explain a large portion of individuals’ speculation buying behavior (37%) and investment buying behavior (21%). Lastly, Multi Group Analysis was conducted to investigate the role of experience (low vs. high). However, no significant difference is found between the two groups. The research contributes to behavioral finance body of knowledge and is of interest to practitioners and scholars alike.